Innovation And Firm's Performance In Malaysia Seberang Perai Region SME's Food Processing Industry - Yong, Cheng Wai (Universiti Sains Malaysia, 2017)
The food and beverage industry of the Small and Medium Enterprise (SMEs) in Malaysia is one of the main drivers for both economic output and employment. Innovation has been recognised as an integral part of business development for firms including the SMEs. There are various innovation types namely marketing innovation, product innovation and process innovation. Each type has different characteristic and fitting for different types of company target. Firms also have many different bases or indicators for evaluating their firm performances namely production performance, marketing performance, innovation performance and financial performance. This paper presents the findings of three case studies from the food industry that are located within the Seberang Perai Municipality, Penang. The objective of this study is to explore the types of innovation practices that SMEs pursue and the performance measures they used to evaluate their firm’s performances. The impact of the innovation types chosen by the firms on the firm performance, namely sales is also identified. Face-to-face interviews are arranged and the survey questionnaires are distributed to managers or owner managers of the selected SMEs. From the case studies, all the three firm samples adopt product, process and marketing innovation. The firms adopt different types of innovation to suit their company needs. Two of the firms tend to focus more on marketing innovation than other types of innovation. On the other hand, all the three firms in this case study also adopt production, marketing, innovation and financial performances to evaluate their firm performances. Similarly, the type of main performance measures used by the companies are different to their company needs. Furthermore, it is found that years of establishment plays an important role in the type of innovation and the performance measures firms pursue. Moreover, it is seen that the innovation initiatives taken by the companies have positive impact on sales. The outcome of this case study provides an understanding of the types of innovation SMEs pursue and its impact on performances. The outcome shows the important role of innovation plays in fueling the growth of the SMEs. It is able to help government to design and offer the appropriate type of assistance to the SMEs.